A systematic review of the comparative pragmatic differences in conversational skills of individuals with autism. (September 2018) - Ying Sng, Cheong; Carter, Mark; Stephenson, Jennifer
Background and aims: Given that problems with social interaction and communication are defining features of autism spectrum disorder, it stands to reason that individuals with autism spectrum disorder have difficulties in conversation. There is a growing body of research on the conversation skills of individuals with autism spectrum disorder, including research conducted to compare these skills to those of typically developing individuals and those with other disabilities. Such comparisons may offer insight into the extent to which conversational skills may be deficient and whether deficits are unique to a particular diagnostic group. Main contribution: This review provides an examination of comparative studies of pragmatic aspects of conversation that included individuals with autism spectrum disorder. Only a small number of consistent findings emerged from the analysis. Groups with autism spectrum disorder find it difficult to stay on topic and provide novel, relevant information. They also tend to perseverate more and initiate and respond less during conversation but, contrary to expectation, similar numbers of turns were offered to partners, and there was little difference in the way communication breakdowns were repaired or clarified. There was a contradictory finding on the use of eye gaze. Conclusions and implications: Some consistent findings were reported but overall, fewer than expected between group differences were found. The fragmented nature of the research and inconsistent operational definitions of variables measured made analysis problematic. Further research and replication of studies is recommended before definitive conclusions can be drawn.